Determination of total antioxidant capacity in plasma by cyclic voltammetry. Two case reports - Psotová, J; Zahálková, J; Hrbác, J; Simánek, V; Bartek, J (Biomedical papers of the Medical Faculty of the University Palacky, Olomouc, Czechoslovakia, 2001)
The cyclic voltammetry (CV) was used for the measurement of the plasma total antioxidant capacity from two types of patients. The first one consisted of 29 volunteers (men aged 18-21 years) who were administered placebo or silymarin at a dose of 858 mg/day. After two months of silymarine administration, CV revealed a statistically significant increase in total antioxidant capacity compared to placebo. No statistically significant changes in TBARS, SH-groups, creatininin, urea, and uric acid concentrations were found. The second group under study comprised 49 patients with chronic renal disease during dialysis therapy. After dialysis, CV revealed a decrease of total antioxidant capacity in the plasma, which was equivalent to a decrease in creatinine, urea and uric acid. CV was performed using a system consisting of a working glassy carbon electrode, an auxiliary platinum electrode, and a reference saturated calomel electrode; a linear change of voltage of 200 mV/s was applied. CV is a simple and relatively reliable method for assessment of body antioxidant status. It is also time and cost effective.
Keywords: Kidney Diseases; antioxidancia; Male; chronická nemoc; dialýza ledvin; Adult; dospělí; nemoci ledvin; mužské pohlaví; Electrochemistry; referenční hodnoty; Chronic Disease; Blood; Reference Values; Renal Dialysis; lidé; elektrochemie; Antioxidants; Humans; krev